2012
DOI: 10.1002/jor.22267
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model of the effect of combined glenohumeral bone defects on anterior shoulder instability: A finite element approach

Abstract: ABSTRACT:The presence of either a Hill-Sachs or a bony Bankart defect has been indicated as a possible cause of subluxation and anterior shoulder dislocation. Previous studies investigated only the effects of isolated humeral or glenoid defects on glenohumeral instability. We investigated the effects on shoulder stability of both glenoid and humeral defects in the glenohumeral joint. A computerbased finite element approach was used to model the joint. A generic model was developed for cartilage and bone of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…16 The 2 humerothoracic positions selected for simulation of joint stability were 45 and 90 , representing the testing angles for abduction of 30 and 60 of glenohumeral abduction, respectively. 7,12 In addition, rotation angles were tested between the range of 40 of internal rotation (IR) and 60 of external rotation (ER).…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The 2 humerothoracic positions selected for simulation of joint stability were 45 and 90 , representing the testing angles for abduction of 30 and 60 of glenohumeral abduction, respectively. 7,12 In addition, rotation angles were tested between the range of 40 of internal rotation (IR) and 60 of external rotation (ER).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…To our knowledge, only a single study investigated the combined defects at 45 and 90 abduction angles only and showed that instability is increased because of the combined defects. 12 Our study aimed to quantify the effect of different size combinations of Hill-Sachs defects and bony Bankart defects on shoulder instability for a broad range of motion. We hypothesized that the bony Bankart lesion and the Hill-Sachs defect would differently contribute to shoulder instability with respect to the arm position.…”
mentioning
confidence: 99%
“…26 The point of dislocation was determined as the position where the most medial part of the humeral head reaches the most lateral part of the glenoid surface. 30,49 …”
Section: Methodsmentioning
confidence: 99%
“…Indications vary with patient and surgeon factors, but a defect that affects over 20%-25% of the glenoid surface area tends to be associated with higher rates of redislocation following repair of soft tissue only (19). Furthermore, concomitant bony Bankart and Hill-Sachs lesions reduce stability more than either in isolation (22).…”
Section: Anterior Shoulder Dislocationmentioning
confidence: 98%